Thermal epimerization of inositol 1,3-benzylidene acetals in the molten state - Gurale, Bharat P.; Krishnaswamy, Shobhana; Vanka, Kumar; Shashidhar, Mysore S. (Tetrahedron, 2011)
1,3-O-Benzylidene-2,4,5,6-tetra-O-substituted-myo-inositol derivatives obtained by the DIBAL-H reduction of the corresponding myo-inositol 1,3,5-orthobenzoate derivatives undergo epimerization at the acetal carbon on heating, in the molten state, just above their melting point. The same epimerization reaction does not proceed either in the crystalline state or in solution. DFT calculations suggest that the epimeric acetal obtained by this thermal process is relatively more stable than the starting acetal. Either of these acetals could not be obtained by the reaction of the corresponding inositol derived diol with benzaldehyde. These observations constitute a novel reaction solely in the molten state, which are rarely encountered in the literature. X-ray crystal structures of the epimeric acetals as well as their radical deoxygenation reaction are also reported. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: cyclitols; Deoxygenation; Epimerization; Melt; Xanthate

Theoretical study of metal-metal cooperativity in the homogeneous water gas shift reaction - Kuriakose, Nishamol; Kadam, Shantanu; Vanka, Kumar (Inorganic Chemistry, 2012)
The possibility of metal-metal cooperativity in improving the yield of the homogeneous water gas shift reaction (WGSR) has been investigated through full quantum mechanical density functional theory calculations. The calculations indicate that bimetallic catalysts would be likely to be more highly active than mononuclear metal-based catalysts for the WGSR. The results have implications for the design of improved WGSR catalysts in the future.

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Transmetallation vs adduct: diverse reactivity of N,O-ketiminato germylene with [Cp*MCl2](2) (M = Rh or Ir; Cp* = eta(5)-C5Me5) and MCl5 (M = Nb and Ta) - Raghavendra, Beesam; Bakthavachalam, K.; Das, Tamal; Roisnel, Thierry; Sen, Sakya S.; Vanka, Kumar; Ghosh, Sundargopal (Journal of Organometallic Chemistry, 2020)
The reactions of the germylenes, [(Dipp)NCMeCHCORGeCl] (1a: R = Me, 1b: R = Ph) with [Ir2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] led to the formation of the adducts [(Dipp)NCMeCHCORGeClIrCl2Cp*] (3a: R = Me and 3b: R = Ph). On the other hand, [Rh2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] does not react with the germylenes (1a and 1b). When the reactions of 1a and 1b are carried out with [Cp*TaCl4], the reaction led to decomposition. The reaction of 1a or 1b with TaCl5 yielded the transmetallated products [(Dipp)NCMeCHCORTaCl4] (4a: R = Me, 4b: R = Ph) with the extrusion of GeCl2. Our theoretical studies show that for, the insertion of TaCl5 to 1a and the formation of 4a with concomitant elimination of GeCl2 is energetically favourable. Extrusion of SnCl2 is also observed when the corresponding stannylene, [(Dipp)NCMeCHCOMeSnCl] was reacted with TaCl5. All these compounds have been characterized by H-1 and C-13 NMR spectroscopy, elemental analysis and the constitution of compounds 1b, 3b, and 4a were confirmed by single-crystal X-ray crystallography. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Adduct formation; Germylenes; Iridium; Ketoiminate; Tantalum; Transmetallation

Tris-heteroleptic ruthenium(II) polypyridyl complexes: Synthesis, structural characterization, photophysical, electrochemistry and biological properties - Bhat, Satish S.; Kumbhar, Avinash S.; Purandare, Neeraja; Khan, Ayesha; Grampp, Gunter; Loennecke, Peter; Hey-Hawkins, Evamarie; Dixit, Ruchi; Vanka, Kumar (Journal of Inorganic Biochemistry, 2020)
{Three water-soluble tris-heteroleptic ruthenium(II) polypyridyl complexes [Ru(bpy)(phen)(bpg)](2+) (1), [Ru (bpy)(dppz)(bpg)]2+ (2), and [Ru(phen)(dppz)(bpg)]2+ (3) (where bpy = 2,2'-bipyridine
Keywords: Circular dichroism; Cytotoxicity; fluorescence; Polypyridyl; ruthenium

Total synthesis of the pseudoindoxyl class of natural products - Dhote, Pawan S.; Patel, Pitambar; Vanka, Kumar; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2021)
The pseudoindoxyl sub-structural motif, amongst the large set of the indole class of alkaloids, represents a unique subset of the oxygenated indole class of the alkaloid family. A majority of this class of natural products contains complex bridged/polycyclic scaffolds with interesting biological profiles. They are thus attractive synthetic targets. Starting from 1963, twenty-eight natural products having the pseudoindoxyl scaffold have been isolated, among which the synthesis of 13 natural products has been accomplished. In this review, we highlight the completed as well as the formal total synthesis of the natural products with a spiro-pseudoindoxyl ring, with a focus on their development. The challenges and the future perspective based on the recent developments in the field will also be discussed. We strongly believe that this review will not only update but also attract the attention of researchers in dealing with the synthesis of pseudoindoxyl compounds.

Tridentate NacNac stabilized tin and nickel complexes: access to a monomeric nickel hydride and its catalytic application - Pahar, Sanjukta; Sharma, Vishal; Mahata, Biplab; George, Christy P.; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2022)
The transmetalation reaction of picolyl-supported tridentate nacnac germylene monochloride [2,6-iPr2-C6H3NC-(Me)CHC(Me)NH(CH2py)]GeCl (1) (py = pyridine) with SnCl2 results in an analogous stannylene chloride (2). The three -coordinated stannylenium cation [{2,6-iPr2-C6H3NC(Me)CHC-(Me)NH(CH2py)}Sn]+ with SnCl3- as a counteranion (3) has been generated through the abstraction of chloride ligand from 2 using an additional equivalent of SnCl2. Instead of forming a donor-acceptor complex, 2 undergoes a facile redox trans-metalation reaction with Ni(COD)2 (COD = cyclooctadiene) and CuCl to afford analogous nickel and copper complexes [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]MCl [M = Ni (4) and Cu (5)]. The reactions of 4 with potassium tri-sec-butylborohydride (commonly known as K-selectride) and AgSbF6 provide access to monomeric Ni(II) hydride, [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]NiH (6) and a Ni(II) cation, [{2,6-iPr2- C6H3NC(Me)CHC(Me)NH(CH2py)}Ni][SbF6] (7), respectively. 6 was found to be an effective catalyst for the hydroboration of amides.

Taming the parent oxoborane - Kundu, Gargi; Amrutha, P. R.; Raj, K. Vipin; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Chemical Science, 2023)
Despite recent advancements in the chemistry of multiply bound boron compounds, the laboratory isolation of the parent oxoborane moiety, HBO has long remained an unsolved and well-recognized challenge. The reaction of 6-SIDipp(.)BH3 [6-SIDipp = 1,3-di(2,6-diisopropylphenyl)tetrahydropyrimidine2-ylidene] with GaCl3 afforded an unusual boron-gallium 3c-2e compound (1). The addition of water to 1 resulted in the release of H-2 and the formation of a rare acid stabilized neutral parent oxoborane, LB(H)]O (2). Crystallographic and density functional theory (DFT) analyses support the presence of a terminal B=O double bond. Subsequent addition of another equivalent of water molecule led to hydrolysis of the B-H bond to the B-OH bond, but the `B=O' moiety remained intact, resulting in the formation of the hydroxy oxoborane compound (3), which can be classified as a monomeric form of metaboric acid.

Taming XeO3 with aza-crowns: computational studies into σ-hole mediated host-guest interactions - Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2024)
Various aza-crowns with different sizes and substituents have been explored computationally as potential hosts for stabilizing the explosive guest xenon trioxide (XeO3) through sigma-hole-mediated aerogen bonding interactions. Interestingly, aza-crowns demonstrate superior binding towards XeO3 compared to their oxygen and thio counterparts. However, unlike the latter cases, where the binding was found to be increasingly favorable with the increase in the size of the crowns, aza-crowns exhibit a variable size preference for XeO3, peaking with aza-15-crown-5, and reducing thereafter with increase in crown size.
Keywords: aza-crowns; host-guest systems; noncovalent interactions; sigma (sigma) hole; Xenon

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac